Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Pasien Sebagai Upaya Meningkatkan Loyalitas - NS Wahdi (Jurnal Ilmiah Aset, 2008)
Recently there is change in service paradigm which is given by a hospital viewed from society and manager. The orientation of service is one of the strategies that must be run by a hospital to achieve patient’s loyalty will can be realized. This research examines the factors that influence patient’s satisfaction an effort to improve patient’s loyalty. In this research, the patient’s satisfaction has variable of patient’s loyalty. The object and location of this research is Panti Wilasa “Citarum” hospital, Semarang,which is located on Citarum street number 98 Semarang. The population and the sample is inpatientthat is 100 patients. The technique of collecting data in this research is questionnaire by using Likert scale of 10 point from “don’t agree” to “do agree”. The analysis tool in this research is Structural Equation Modeling (SEM) from AMOS software version 5.0. From the research shows that not all hypotheses can be accepted, it shows that not all variables influence directly to loyalty. The service quality has significant influence to patient’s satisfaction and patient’s loyalty. The patient’s satisfaction has significant influence to loyalty, the variable of life satisfaction shows, there is no significant influence to patient’s satisfaction. So from the fourth hypotheses, there is only one hypothesis that can’t be proved, that is variable of life satisfaction to patient’s satisfaction. This confirms most researches used to examine the similar theme by more specific model and object.